How Does the Influence of Moral Values Affect Children's Use of Roblox in Character Education? - Damanhuri; Wali, Muhammad (Lembaga KITA, 2024)
This experimental study evaluated the effectiveness of Roblox game design based on local Indonesian values in strengthening character education for children aged 9-12 years through a mixed-methods approach. Involving 320 participants from 15 schools in Aceh Province, this study measured behavioral changes using the Moral Competence Game Scale (MCGS-α=0.87) and analyzed 1,250 transcripts of game interactions over a 12-week period. Quantitative results showed a significant increase in prosocial behavior (42%, p<0.01) and conflict resolution competence (d=0.63), while qualitative analysis revealed the dominance of collaborative communication patterns (78%) in the avatar rescue scenario. The integration of local wisdom such as mutual cooperation simulations in shared resource management mechanics, adaptation of local Acehnese games, and deliberation-based narratives were shown to increase the retention of justice values by 28% compared to generic content. The main challenges included exposure to 23% of morally ambiguous content and technostress in 65% of parents, which were addressed through the Onion-Layer Protection model combined with AI moderation and community reporting. The research implications resulted in Ethical Design Guidelines for local game developers that include technical parameters such as 30% memory usage optimization with 1:1 trim sheet technique and 15% FPS increase through adaptive LOD system.